Diketahui fungsi f: R -> R dengan f(x) = x2-4x+2 dan fungsi g: R ->R dengan g(x)

Diposting pada

Diketahui fungsi f: R -> R dengan f(x) = x2-4x+2 dan fungsi g: R ->R dengan g(x) = 3x-7
ditanya
a. (g°f) (x)
b. (f°g) (x)
c. (g°f) (5)
d. (f°g) (10)

Jawaban
a. (gof)(x) = 3(f(x)) – 7
= 3(x² – 4x + 2) – 7
= 3x² – 12x + 6 – 7
= 3x² -12x – 1

b. (fog)(x) = (g(x))² – 4(g(x) + 2
= (3x – 7)² – 4(3x – 7) + 2
= 9x² -42x + 49 -12x + 28 + 2
= 9x² – 54x + 79

c. (gof)(5) = 3(5)² – 12(5) – 1
= 3(25) – 60 – 1
= 75 – 61
= 14

d. (fog)(10) = 9(10)² – 45(10) + 79
= 9(100) – 450 + 79
= 900 – 371
= 529

 

Tinggalkan Balasan

Alamat email Anda tidak akan dipublikasikan.